English English - Siti Nur Ramdaniati; E. Egriana Handayani; Dedeh Jubaedah (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
Safety Behavior is a way of behaving that is carried out by individual interest to minimize or prevent potential disasters. Safety behavior in this research focuses on the human behavior aspect in workplace accidents. The purpose of this study is to determine the relationship between knowledge, attitudes, and compliance with the use of Personal Protective Equipment (PPE) with safety behavior among SPBE Pertamina employees in Pandeglang District. This research uses quantitative methods by cross-sectional and observation approach to the study. The sample of this research is all of the 40 employees in SPBE working in charge of Liquefied Petroleum Gas (LPG) filling. Total sampling is used as a sample retrieval technique, and the data retrieval technique used is a questionnaire. The data analysis method used is univariate and bivariate analysis with Chi-Square test analysis. The result of this study shows a significant relationship between knowledge of the safety behavior of SPBE employees (p-value 0.034) and there is a significant relationship between attitude with SPBE employees' safety behavior (p-value 0.011). This study concludes that there is a relationship between knowledge and attitude toward safety behavior among SPBE Pertamina employees in the Pandeglang District. Therefore, it is suggested that SPBE leadership conduct education for employees so that employee knowledge and attitudes increase so that they can increase good safety behavior for employees.